Comparative Analysis of the Fecal Microbiota of Wild and Captive Beal’s Eyed Turtle (Sacalia bealei) by 16S rRNA Gene Sequencing - Fong, Jonathan J.; Sung, Yik-Hei; Ding, Li (Frontiers in Microbiology, 2020)
The Beal’s eyed turtle (Sacalia bealei) is threatened with extinction due to hunting for large-scale trade. In Hong Kong, there are some of the world’s remaining wild populations of S. bealei, as well as a breeding colony. This breeding colony is at the core of conservation efforts (captive breeding, reintroduction programs). Therefore, we would like to know how captivity, in particular diet, affects the gut microbiota. Using high-throughput 16S rRNA gene sequencing, we comparatively analyzed the fecal microbiota of wild and captive S. bealei. We found that wild S. bealei have higher alpha diversity than captive S. bealei, but the difference was not significant. Significant differences were found in β-diversity; at the phylum level, wild S. bealei have higher relative abundances of Proteobacteria and captive S. bealei have higher relative abundances of Firmicutes. At the genus level, Cetobacterium and Citrobacter are more abundant in wild S. bealei, while Clostridium spp. are significantly more abundant in captive S. bealei. These results suggest conditions in captivity, with diet being a major factor, influence the gut microbiota of S. bealei. The connection between diet and health has always been considered for captive animals, and in this study we use the gut microbiota as an another tool to assess health.